Transport and sensors properties of nanostructured antimony-doped tin oxide films - Giraldi, T. R.; Escote, M. T.; Maciel, A. P.; Longo, Elson [UNESP]; Leite, E. R.; Varela, José Arana [UNESP] (Elsevier B.V., 2006)
Tin oxide thin films doped with 7 mol% antimony oxide multilayer were prepared by the polymeric precursor method. Morphological characterization revealed films with round-shaped grains, nanometric size (similar to 13 nm), and low roughness. These films display high transmittance (similar to 80%) in the visible range of transmittance spectra, which is desirable for transparent conductive oxide films. Analysis on electrical resistivity versus temperature data showed two different conduction mechanisms toward the temperature range. The gas sensor properties measurement of the thicker thin film revealed good sensibility for the NOx. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: tin oxide; polymeric precursor; variable-range hopping; gas sensors